2018
DOI: 10.1109/tia.2018.2859173
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Axial Flux Magnetically Geared Machine for Power Split Application

Abstract: This paper proposes an axial flux magnetically geared (AFMG) permanent magnet (PM) machine for power split application in hybrid electric vehicles (HEVs). The proposed AFMG machine has the merits of simple structure and improved torque density by combining a magnetic gear (MG) with a PM machine. The machine can realize power split with the help of dual mechanical ports and one electrical port, i.e., the input mechanical power and/or electrical power produced by the machine can be split or integrated. The opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Based on the concept of PSs, numerous other types of PS machines can be developed, e.g. doubly fed dual‐stator reluctance and induction machines as mentioned in Section 2 [20–23], linear/tubular [110, 111] and axial‐field [112–115] PS machines, as well as PS memory machines [116] based on the concept of online magnetising and demagnetising PMs [117–120]. However, due to space limit, they are not being reviewed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the concept of PSs, numerous other types of PS machines can be developed, e.g. doubly fed dual‐stator reluctance and induction machines as mentioned in Section 2 [20–23], linear/tubular [110, 111] and axial‐field [112–115] PS machines, as well as PS memory machines [116] based on the concept of online magnetising and demagnetising PMs [117–120]. However, due to space limit, they are not being reviewed in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the surface-type FMPM machines can also be designed with axial flux, which are even more promising in achieving compact structures and high torque densities. Figure 9 shows the configuration of an axial-flux MGPM machine for power split application in hybrid electric vehicles [24], and comparative investigation showed that it can achieve significantly higher torque than the conventional axial-flux YASA machine [25]. The application of an axial-flux MGPM machine in a wind turbine was investigated in [26], and a prototype with a torque density of 7.8 kNm/m 3 was designed, fabricated, and tested.…”
Section: Surface-type Fmpm Machinesmentioning
confidence: 99%
“…In [14], an AMG with superconducting bulk magnets was presented, which increased the torque density at the expense of higher manufacturing costs. In [15], a new axial-flux magnetically geared permanent magnet machine was proposed for power split application in a hybrid electric vehicle. Kouhshahi et al [16] have proposed a novel magnetically geared generator for low-speed applications with a torque density of 114 kNm/m 3 .…”
Section: Introductionmentioning
confidence: 99%